INTERVENSI NON FISIK TEMPAT PEMBUANGAN SAMPAH DI DESA TABONGO KECAMATAN DULUPI - Tolinggi, Safrudin; Dengo, Moh Rivandi; Arda, Zul Adhyani; Latala, Novita (LPPM Institut Pendidikan Nusantara Global, 2022)
Tabongo Village is located in Dulupi District, Boalemo Regency. The village boundaries with Dulupi Village in the west, Kota Raja & Polohungo Villages in the north, and the Tomini Sea in the east with a total population is around 1.038 people in 2021. The population density in Tabongo has increased a potential disease caused by rubbish heaps in any place which caused a flood, this problem will be solved by people’s attention to clean and healthy living behavior approach. Rubbish is a problem that is now faced by all surrounding communities. This waste develops along with the increase in population and the increase in development activities carried out by the community. The current waste problem is not only a problem in big cities but also in villages. The habit of littering is carried out in almost all circles of society, not only the poor, but even those with higher education also do it. Bad behavior is getting worse because of the lack of cleanliness that is easily accessible by the public in public places. The purpose of this service is to find out the optimization of the procurement of pilot trash bins in order to increase the number of trash bins so that they can overcome the lack of trash bins in Tabongo Village